Driving the COVID-19 Response from the Center : Institutional Mechanisms to Ensure Whole-of-Government Coordination - Kunicova, Jana (World Bank, Washington, DC, 2020)
Facing the COVID-19 (coronavirus) pandemic, governments around the world have set up various coordination mechanisms at the center of government (COG) to facilitate pandemic response. The broader COG literature provides some important lessons for the coordination during COVID-19 pandemic. This working paper is part of the Governance and Institutions COVID-19 Rapid Response series spearheaded by the Governance Global Practice, World Bank. The paper presents initial thinking and uses immediately available data, as it aims to document the emerging knowledge, provide the grounds for just-in-time policy and institutional advice to governments, and suggest avenues for further research.